PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP PENGETAHUAN KONSEPTUAL SISWA POKOK BAHASAN SUHU DAN KALOR FISIKA SMK KELAS X SEMESTER II T.P 2015/2016 - Lisnayanti, Lisnayanti (JURNAL IKATAN ALUMNI FISIKA, 2017)
This study aims to determine the conceptual physics students learning outcomes on temperature and heat subject matter. The sampling technique was conducted in cluster random sampling. Experimental class was a class X TPTU-2 and the control class was a class X TSM-1 consist 35 students each of classes. The instrument used was a multiple choice tested on students conceptual ability about 20 multiple choice questions. The gain value of cooperative learning model typed Group Investigation 0.29 included in the moderate category and the conventional learning was 0.12 included in the low category. Proved from hypothesis tested in cooperative learning model typed Group Investigation towards students conceptual ability was better than conventional learning in class X semester II of SMK in temperature and heat subject matter.